Combination of p16INK4a/Ki67 immunocytology and hpv polymerase chain reaction for the noninvasive analysis of HPV involvement in head and neck cancer. Issue 4 (29th December 2014) - Linxweiler, Maximilian; Bochen, Florian; Wemmert, Silke; Lerner, Cornelia; Hasenfus, Andrea; Bohle, Rainer Maria; Al‐Kadah, Basel; Takacs, Zoltan Ferenc; Smola, Sigrun; Schick, Bernhard
<x xml:space="preserve">Abstract</x> BACKGROUND High‐risk human papillomavirus (HPV) infection has been identified as a relevant risk for the development of head and neck squamous cell carcinomas (HNSCCs). As HPV status has also gained a role as a prognostic and predictive biomarker for this entity, there is a growing demand for valid HPV testing in HNSCC patients METHODS Liquid‐based cytological smears from 45 HNSCC and 20 control patients were collected and used for simultaneous immunocytochemical p16INK4a/Ki67 staining using a CINtec PLUS kit after the presence of tumor cells was verified in a Papanicolaou‐stained slide. The same cytological suspension was used for the detection of HPV DNA by specific polymerase chain reaction (PCR). RESULTS Tumor cells were detected in the swab material of 44 HNSCC patients corresponding to a sensitivity of 98% (44 of 45). PCR analysis revealed the presence of HPV DNA in the cytological suspension of 13 patients (13 of 65, 20%) with simultaneous p16INK4a/Ki67 expression by the tumor cells in 11 of these HPV DNA–positive samples (11 of 13, 85%) — a staining pattern that is strongly associated with a carcinogenic HPV infection. CONCLUSIONS A simultaneous immunocytochemical detection of p16INK4a and Ki67 can reliably be performed on liquid‐based cytological smears from HNSCC patients using a CINtec PLUS kit. In addition, the same cytological material can be used for the detection of HPV DNA by specific PCR. The combined results of both techniques enable better discrimination between latent and carcinogenic HPV infections as well as HPV‐negative cases and thus can provide information on the prognosis of HNSCC patients and facilitate therapeutic decisions. Cancer (Cancer Cytopathol) 2015;123:219–229. © 2014 American Cancer Society.